Metodologia para mensuração da maturidade tecnológica em bioinsumos - MTBIO: uma contribuição para a transferência de tecnologia - Lorenzoni, Lauren Peres (2024)
Innovation drives economic growth, and universities play a fundamental role in the advancement of science and technology. Encouraging the transfer of knowledge to society is part of the mission of universities, and in this context, Technology Innovation Centers (TICs) play a crucial role in making this happen effectively. Thus, there arises the need to improve the processes involved in technology transfer. The bioinputs market is rapidly expanding, and the trend within universities is that research and development of cutting-edge technologies in this area will also grow exponentially. Therefore, the general objective of this research is to propose a methodology for measuring technological maturity in bioinputs, to be used in TICs. The development of a methodology to assess the technological maturity of bioinputs is crucial for the success of transferring this technology. This is because one of the main concerns of companies is to understand the level of technological readiness of these products. This understanding allows companies to more accurately assess the time required, the financial resources involved, as well as the uncertainties and technical risks associated with the technology transfer process. To develop the methodology, a systematic literature review was initially conducted to establish the framework for the bioinput development cycle. Then, to provide greater specificity to this cycle, the expert panel method was employed in conjunction with the Delphi Method to precisely define the phases and specific stages of bioinput development for biological control. Subsequently, in order to weigh these phases and stages and assess the level of importance attributed to each of them, the expert panel was consulted again, this time in conjunction with the SWARA method. This approach provided a thorough and refined analysis of the fundamental parts of the process. Finally, the proposed methodology was applied to bioinputs developed within the university. This allowed for an accurate verification of the development percentage of each bioinput, as well as the determination of the specific stage in which they are located. This practical application demonstrated the effectiveness of the methodology and its alignment with the objectives established in this thesis.